Chiral terpene auxiliaries III: spiroborate esters from (1R, 2S, 3R, 5R)-3-amino-apopinan-2-ol as highly effective catalysts for asymmetric reduction of ketones with borane. Issue 24 (31st December 2015) - Ćwiklińska, Marta; Krzemiński, Marek P.; Tafelska-Kaczmarek, Agnieszka
Graphical abstract: Abstract: New spiroborate esters, derived from terpene amino alcohols, ( S )-prolinol, and 2-aminoethanol, were employed as catalysts in the borane reduction of acetophenone and other aryl alkyl and halogenated ketones. The corresponding alcohols were obtained in high yields and with enantioselectivities up to 98% ee. The influence of the amino alcohol and the diol moieties of spiroborate on the reaction selectivity was examined. The catalyst load, the nature of the solvent, the borane source, and the reaction conditions were also investigated. Abstract : (1 R, 2 S, 3 R, 5 R )-2-(1′, 3′, 2′-Dioxaborolan-2′-yloxy)-apopinan-3-amine: C11 H20 BNO3 Ee = 99% [ α ]D 20  = −23.8 ( c 0.5, THF) Source of chirality: asymmetric synthesis Absolute configuration: (1 R, 2 S, 3 R, 5 R ) Abstract : (1 R, 2 S, 3 R, 5 R )-2-(1′, 3′, 2′-Dioxaborolan-(4′-2, 5′-3-(1 R, 2 R, 3 S, 5 R )-pinan)-2′-yloxy)-apopinan-3-amine: C19 H32 BNO3 Ee = 99% [ α ]D 20  = −20.6 ( c 0.6, THF) Source of chirality: asymmetric synthesis Absolute configuration: (1 R, 2 S, 3 R, 5 R ) Abstract : (1 R, 2 S, 3 R, 5 R )-2-(1′, 3′, 2′-Dioxaborolan-(4′-3, 5′-4-(1 S, 3 S, 4 R, 6 R )-caran)-2′-yloxy)-apopinan-3-amine: C19 H32 BNO3 Ee = 99% [ α ]D 20  = −17.5 ( c 0.6, THF) Source of chirality: asymmetric synthesis Absolute configuration: (1 R, 2 S, 3 R, 5 R ) Abstract : (1 R, 2 S, 3 R, 5 R )-2-(1′, 3′, 2′-Dioxaborolan-(4′-3, 5′-4-tetrahydrofuran)-2′-yloxy)-apopinan-3-amine: C13 H22 BNO4 Ee = 99% [ α ]D 20  = −28.5 ( c 0.6, THF) Source of chirality: asymmetric synthesis Absolute configuration: (1 R, 2 S, 3 R, 5 R ) Abstract : (1 R, 2 S, 3 R, 5 R )-2-(1′, 3′, 2′-Dioxaborolan-(4′-1, 5′-2-cyclopentan)-2′-yloxy)-apopinan-3-amine: C14 H24 BNO3 Ee = 99% [ α ]D 20  = −17.0 ( c 0.5, THF) Source of chirality: asymmetric synthesis Absolute configuration: (1 R, 2 S, 3 R, 5 R ) Abstract : (1 S, 3 S, 4 R, 6 R )-3-(1′, 3′, 2′-Dioxaborolan-2′-yloxy)-caran-4-amine: C12 H22 BNO3 Ee = 99% [ α ]D 20  = −2.2 ( c 0.5, THF) Source of chirality: asymmetric synthesis Absolute configuration: (1 S, 3 S, 4 R, 6 R ) Abstract : (1 S, 2 S, 3 S, 4 S, 5 R )-3-(1′, 3′, 2′-Dioxaborolan-2′-yloxy)-2-methoxy-pinan-4-amine: C13 H24 BNO4 Ee = 99% [ α ]D 20  = +33.3 ( c 0.6, THF) Source of chirality: asymmetric synthesis Absolute configuration: (1 S, 2 S, 3 S, 4 S, 5 R ) Abstract : ( S )-2-[(1, 3, 2-Dioxaborolan-(4-2′, 5-3′-(1′ S, 2′ S, 3′ R, 5′ S )-pinan)-2-yloxy)-methyl]pyrrolidine: C15 H26 BNO3 Ee = 99% [ α ]D 20  = +22.95 ( c 0.6, THF) Source of chirality: asymmetric synthesis Absolute configuration: ( S )(1′ S, 2′ S, 3′ R, 5′ S ) Abstract : ( S )-2-[(1, 3, 2-Dioxaborolan-(4-2′, 5-3′-(1′ R, 2′ R, 3′ S, 5′ R )-pinan)-2-yloxy)-methyl]pyrrolidine: C15 H26 BNO3 Ee = 99% [ α ]D 20  = +22.0 ( c 0.5, THF) Source of chirality: asymmetric synthesis Absolute configuration: ( S )(1′ R, 2′ R, 3′ S, 5′ R ) Abstract : 2-(1, 3, 2-Dioxaborolan-(4-2′, 5-3′-(1′ R, 2′ R, 3′ S, 5′ R )-pinan)-2-yloxy)-ethanamine: C12 H22 BNO3 Ee = 99% [ α ]D 20  = −26.4 ( c 0.5, THF) Source of chirality: asymmetric synthesis Absolute configuration: (1′ R, 2′ R, 3′ S, 5′ R )